EFL Secondary Students’ Perceptions on Native and Nonnative English-Speaking Teachers - Tjokrokanoko, Angelia; Tedjasuksmana, Hendra (Widya Mandala Catholic University Surabaya, 2013)
This study examined the secondary students’ perceptions towards NESTs and NNESTs in an English course in Surabaya regarding the teachers’ teaching competence, cultural knowledge of English language teaching, teaching style, and classroom management. Most secondary students perceived both teacher groups were good at most categories. Using questionnaires distributed to 96 secondary school students of an English course who participated in this study, the researchers found that 38 students took part in doing a focus group interview. The interview was done to capture deeper perceptions that could be gained. The study reported that cultural knowledge of the English language teachers, especially the NESTs, exceeded that of the NNESTs. This research finding also proved that students perceived NESTs to be as good as NNESTs in such areas as teaching grammar, listening, reading, and writing. Furthermore, both NESTs and NNESTs were perceived to be not able to understand the students’ special needs since teachers at the the English course under study handled one level for about twelve meetings only.